(untitled) (Sciences & Technologie. C, Biotechnologies, 2014)
In order to define the isolation conditions of actinomycetes from desert soils, the soils of the town of Biskra, situated at the gate of the Algerian Sahara was analyzed. Two types of samples have been prepared; the firt one was heated up at 110 °C during 10 minutes and the second did not undergo any heat processing. The isolation was carried out from these two types of soils on the starch casein medium added to a combination of several antifungal and antibacterial agents. Five different isolation mediums have been tested in this study. The results showed that the pretreatment of the soil with heat is not recommended. Indeed, the number of isolated actinomycetes was 38. 104 cfu.g-1 when the soil samples were heated up and 92.104 cfu.g-1 when no heating was used. The thermic processing reduces then the actinomycetes by more than 50 %. The antifungal and antibacterian which permit the elimination of undesirable germs are the nystatin and the nalidixic acid with respective concentrations of 50 µg/ml and 10 µg/ml. According to these results, the most favorable isolation medium for actinomycetes of desert soils studied is Glucose-yeast extract-malt (GLM).